2nd Nordic NJF Seminar on Reindeer Husbandry Research "Reindeer herding and land use management - Nordic perspectives" - Soppela, Päivi; Kumpula, Jouko; Oinonen, Kari (Rangifer, 2015)
The 2nd NJF Seminar on Reindeer Husbandry Research was held at the Arctic Centre, University of Lapland, Rovaniemi, Finland from 19 to 21 October 2014. The seminar was organised under the framework of Reindeer Husbandry Research Section of NJF (Nordic Association of Agricultural Scientists), established in 2012. Over 100 Nordic and international delegates including researchers, managers, educators, students and reindeer herders participated in the seminar.